Attitudes and barriers to family planning methods among reproductive-age women in Southern Philippines - Flores, Rica; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
The Responsible Parenthood and Reproductive Health Law of 2012 established a framework to promote reproductive health and rights in the Philippines. This study investigates the attitudes and common barriers to family planning among reproductive-age women in Southern Philippines. A quantitative approach was used, with a structured questionnaire administered to 70 women attending prenatal care services in Barangay Lag-asan, Bago City, Negros Occidental. Statistical analysis examined the relationships between attitudes, perceived barriers, and various sociodemographic factors. The findings reveal that the majority of participants maintain positive and optimistic attitudes toward family planning. While factors such as age, religion, family income, education level, duration of marriage, number of pregnancies, and employment status did not significantly influence attitudes, marital status was significantly associated with more favorable perceptions. Additionally, common barriers assessed across emotional, social, and cognitive domains did not significantly differ among the various demographic groups. These results suggest that, overall, positive perceptions prevail, although marital context appears to shape individual attitudes. The insights provided by this study underscore the need for enhanced government initiatives, increased funding, and culturally sensitive educational programs to improve the accessibility and awareness of family planning, ultimately promoting better reproductive and neonatal health outcomes.